Hydrothermal Economic Dispatch Incorporating the Valve Point Effect in Thermal Units Solved by Heuristic Techniques - Katherine Hernández; Carlos Barrera-Singaña; Luis Tipán (Energies)
This document explores short-term hydrothermal economic dispatch (HTED) while explicitly modeling the valve-point effect of thermal units as a factor that adds complexity to power system optimization. Two nature-inspired optimizers, the Bat Algorithm (BAT) and the Artificial Bee Colony (ABC) algorithm, were used on a 24 h horizon for nine unit power plants (five thermal, four hydro). After 30 independent runs, BAT produced the lowest daily operating cost at USD 307,952.44, whereas ABC obtained USD 311,457.48, a 1.14% saving (USD 3.5 k) in favour of BAT. However, ABC converged almost twice as fast, stabilizing after around 40 iterations, while BAT required around 80 iterations. The results demonstrate that BAT offers a modest but measurable economic advantage, whereas ABC provides faster convergence, which is important when real-time computational limits dominate. These quantitative findings confirm that meta-heuristic techniques are practical tools for HTED and highlight the trade-off between cost minimization and computational speed.